Bahrain and the global balance of power after the Arab spring - Lars Erslev Andersen (Danish Institute for International Studies (DIIS), 2012)
The global balance of power is changing, and the role of the US as the only superpower is being challenged by emerging new powers and a still more powerful China. Nowhere is this more apparent than in the Persian Gulf. Two wars in Afghanistan and Iraq and continually rising debt have meant that the position of the US has declined. At the same time, Asian states are increasing their economic expansion in the Persian Gulf. Increasing political influence, including a bigger role in hard security, is following the increasing economic role of Asia. These developments have been consolidated by the Arab Spring, where US support for reform and democracy in Egypt and North Africa has pushed the Arab Gulf states even more towards Asia and to a more wary attitude towards the US. This Working Paper argues that if we are fully to understand these developments we need to analyse the Persian Gulf as a regional security complex in its own right. The argument is developed empirically with reference to the case of Bahrain.
Keywords: 300; Weltordnung; Internationale Politik; Politischer Wandel; Bahrain; Arabische Golf-Staaten